Glucose oxidase and metal organic framework loaded hydrogel and application in bone defect

By developing a network composition containing magnesium ions and polyphenol compounds and combining hydrogel materials with glucose oxidase, the problem of hindered bone regeneration in the diabetic microenvironment is solved, and the promotion effect of bone repair and angiogenesis is achieved.

CN119868650APending Publication Date: 2025-04-25SHANGHAI NINTH PEOPLES HOSPITAL SHANGHAI JIAO TONG UNIV SCHOOL OF MEDICINE
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202311376190.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Bone regeneration in the diabetic microenvironment is hindered by high ROS, hyperglycemia, chronic inflammation and angiogenesis disorders, making it difficult to repair diabetic bone defects.

Method used

A network composition containing magnesium ions and polyphenol compounds, combined with glucose oxidase, is developed to regulate the local diabetes microenvironment, form an injectable, ultraviolet curable and gas-foaming hydrogel material, simulates extracellular matrix and promotes bone repair.

Benefits of technology

This hydrogel material provides an hypoxic environment that promotes vascular formation by regulating the hyperglycemia environment that damages bone regeneration by regulating diabetes, which has the ability to regulate inflammation, promotes bone formation and angiogenesis, and reverses the microenvironment that is not conducive to bone regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868650A_ABST
    Figure CN119868650A_ABST
Patent Text Reader

Abstract

Hydrogel comprises hydroxyapatite nanowires and a base material for forming the hydrogel, and further comprises glucose oxidase (GOx), gallic acid, magnesium ions (Mg < 2 + >) and the like, the gallic acid and the Mg < 2 + > form Mg-MOF, and the GOx is loaded on the Mg-MOF, so that the diabetes microenvironment of a bone defect part is locally adjusted, and bone defect repair is facilitated. Through verification, the sustained-release gallic acid of GOx-MOF participates in cascade reaction, GOx is removed to generate H2O2, the benefit is maximized, and the sustained-release gallic acid has good effects of controlling blood glucose, removing ROS, regulating inflammation and promoting osteogenesis and angiogenesis. The research is expected to play a role in microenvironment regulation of diabetes mellitus bone regeneration and minimally invasive treatment of bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a biomaterial, in particular to a network composition containing magnesium ions and polyphenol compounds, which cooperates with glucose oxidase to regulate the local diabetic microenvironment, and its application in repairing diabetic bone defects and preparing medical devices. Background Art

[0002] Bone regeneration in the diabetic microenvironment is hampered by multiple pathways, such as high levels of ROS, hyperglycemia, chronic inflammation, and angiogenesis disorders. Given the increasing needs of patients, there is an urgent need to develop more effective therapeutic strategies to enhance the repair and regeneration of bone defects in diabetic patients.

[0003] Bone tissue engineering is the current development trend of bone defect repair and bone regeneration, and biomaterial scaffolds are one of the three major elements of tissue engineering technology. In the past, many studies used gelatin methacrylate anhydride (GelMA) as a bone regeneration scaffold to simulate the extracellular matrix and, more importantly, to adjust the pore size and its distribution, which is necessary for cell growth and angiogenesis. Our previous studies have shown that foam gas materials can create pores that are more suitable for cell growth and angiogenesis. However, the fragility of GelMA limits its application in bone regeneration. Summary of the invention

[0004] One object of the present invention is to provide a hydrogel having a concrete-like structure and good hardness, which is conducive to bone repair.

[0005] Another object of the present invention is to provide a hydrogel having the characteristics of being injectable, UV-curable and gas-foamable, and suitable for various adaptive shapes to fill bone defects.

[0006] Another object of the present invention is to provide a hydrogel to reverse the microenvironment in diabetes that is not conducive to bone regeneration and promote bone repair.

[0007] Another object of the present invention is to provide a hydrogel as a medical device for repairing bone defects, especially repairing diabetic bone defects.

[0008] A fifth object of the present invention is to provide a medical device, comprising a hydrogel comprising components such as glucose oxidase, Mg-MOF and hydroxyapatite nanowires, which is suitable for repairing diabetic bone defects.

[0009] A hydrogel, hydroxyapatite nanowires (HAP-NWs), and a base material for forming the hydrogel.

[0010] The basic materials of hydrogels include, but are not limited to, PEG, PLGA-PEG, γ-PGA, ε-PLL, hyaluronic acid, gelatin, chondroitin sulfate and their cross-linked modified derivatives, such as GelMA, HAMA and γ-PGA / ε-PLL (PP) suitable for photo-crosslinking.

[0011] The hydrogel of the present invention has a structure similar to reinforced concrete, improves the hardness of the material and enhances the supporting force of the pore structure, while promoting bone formation. The weight ratio of HAP-NWs to the basic material of the hydrogel is 1:10.

[0012] The hydrogel provided by the present invention uses ultraviolet light-cured hydrogel as a basic material, has the characteristics of being injectable, ultraviolet-curable and gas-foaming, is suitable for filling bone defects in various adaptive shapes, and has good hardness.

[0013] Studies have shown that hydroxyapatite (HAP) can promote the adhesion, proliferation and migration of rat bone marrow mesenchymal stem cells, and increase the protein expression of osteogenesis and angiogenesis genes. HAP is an important component of human skeleton, but compared with the bone healing cycle, artificial HAP degrades too slowly and has certain differences with bone tissue. In this regard, the present invention synthesizes hydroxyapatite nanowires (HAP NWs: a tough HAP fiber), which is more easily degraded and can increase the support of GelMA.

[0014] A specific embodiment of preparing the HAP-NWs of the present invention comprises:

[0015] After mixing water, oleic acid and methanol, add an aqueous solution of NaOH, stir (e.g., for 30 minutes), add CaCl2 and NaH2PO4·2H2O, mix, place at 180°C for reaction for 24 hours, wash (e.g., use ethanol and deionized water alone or in combination) three times and centrifuge to obtain a precipitate.

[0016] Another specific embodiment of preparing the HAP-NWs of the present invention comprises:

[0017] After mixing water, oleic acid and methanol, add aqueous NaOH solution (pH=9) and stir for 30 minutes. Add 3.33g CaCl2 and 9.36g NaH2PO4·2H2O respectively, mix and react at 180℃ for 24 hours, wash (e.g., use ethanol and deionized water alone or in combination) three times and centrifuge to obtain a precipitate.

[0018] Another specific embodiment of preparing the HAP-NWs of the present invention comprises:

[0019] Water (e.g. 135 ml), oleic acid (e.g. 105 ml) and methanol (e.g. 60 ml) are mixed and then an aqueous solution of NaOH (e.g. 150 mL 10.5 g NaOH) is added and stirred for 30 minutes. 3.33 g CaCl2 and 9.36 g NaH2PO4·2H2O are added respectively, mixed and reacted at 180°C for 24 hours, washed (e.g. ethanol and deionized water alone or in combination) three times and centrifuged to obtain a precipitate.

[0020] Repair of diabetic bone defects remains a major clinical challenge, as glucose fluctuations, reactive oxygen species (ROS) damage and inflammatory microenvironment affect the normal process of bone defect repair. The hydrogel provided by the present invention also includes glucose oxidase (GOx), gallic acid and magnesium ions (Mg 2+ ) etc., to locally regulate the diabetic microenvironment at the bone defect site.

[0021] Another hydrogel, including glucose oxidase (GOx), gallic acid and magnesium ions (Mg 2+ ), hydroxyapatite nanowires (HAP-NWs), and basic materials for forming hydrogels.

[0022] The hydrogel of the present invention, magnesium ions (Mg 2+ ) in the form of a metal-organic framework (MOF), namely Mg-MOF, which is carried in the base material of the hydrogel.

[0023] Another hydrogel comprising GOx, gallic acid, Mg 2+ , HAP-NWs, and gelatin methacrylate anhydride (GelMA), gallic acid, and Mg 2+ Mg-MOF was formed, and GOx was loaded on Mg-MOF, which was recorded as: GOx MOF / HAP GelMA.

[0024] The sustained-release gallic acid of GOx-MOF participates in the cascade reaction, avoiding the production of H2O2 by GOx and maximizing its benefits. It has good blood sugar control, scavenges ROS, regulates inflammation, and promotes osteogenesis and angiogenesis.

[0025] The hydrogel of the present invention, by weight, GOx and HAP-NWs are: 1±0.2:2×10 5 .

[0026] The hydrogel of the present invention comprises gallic acid and Mg by weight. 2+ Is: 15±1:1.

[0027] In the hydrogel of the present invention, the ratio of gallic acid to HAP-NWs is 1:42±2 by weight.

[0028] It has been verified that GOx-MOF / HAP-GelMA gas foaming material i) can produce more pores in high-concentration GelMA, allowing cells to grow and improving the hardness of the material; ii) adding HAP-NWs combined with GelMA can form a reinforced concrete structure, further improving the hardness of the material and enhancing the supporting capacity of the pore structure. At the same time, HAP is an important component of human bone, and the Ca and P provided by HAP-NWs promote bone formation; iii) GOx regulates the high blood sugar environment that impairs bone regeneration in diabetes, while providing an oxygen-deficient environment that promotes angiogenesis; iv) Mg-MOF has a strong ability to regulate inflammation. In addition to gallic acid promoting cell proliferation and anti-inflammatory effects, Mg 2+ It also promotes the transformation of macrophage types from M1 to M2. 2+ It has a favorable effect on angiogenesis and bone growth; v) The combined cascade reaction of GOx-MOF effectively reverses the microenvironment in diabetes that is not conducive to bone regeneration: it has an impact on hypoglycemia, hypoxia, ROS scavenging, cell proliferation, angiogenesis and bone growth. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Figure 1 is a diagram of the synthesis and characterization results of Mg-MOF and HAP nanoparticles; wherein, A is a schematic diagram of the synthesis of GOx-MOF, B is an XRD spectrum of Mg-MOF synthesized at 50°C (a), 70°C (b) and 120°C (c), C is an absorption spectrum of GOx, Mg-MOF and GOx-MOF, the Mg-MOF, GOx and GOx-MOF curves correspond to the (a), (b) and (c) curves in B, respectively, and the absorbance at each peak is: a = 260nm; b = 272nm; c = 276nm, D is a standard curve of the Mg-MOF concentration absorption value, E is a schematic diagram of the synthesis process of HAP-NWs, F is a SEM image of HAP-NWs, G is a TEM image of HAP-NWs, H is an XRD spectrum of HAP-NWs powder, and I is an optical photograph of HAP-NWs in deionized water;

[0030] Figure 2Figure 1 is a graph showing the synthesis and characterization results of GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA; A is an optical photograph of four gas foaming materials, B is a SEM image of four gas foaming materials with concentrations of 12.5% ​​and 50%, C is a SEM image of four gas foaming materials with a concentration of 50%, D is a comparison of the mechanical strength of four gas foaming materials, E is an optical image of GOx-MOF / HAP-GelMA pushed out by a syringe, and F is an optical image of UV-cured Optical photographs of GOx-MOF / HAP-GelMA after curing, G is a degradation curve of four gas foaming materials for 28 days, H is a glucose degradation curve of four gas foaming materials for 48 hours, without these materials as a control group (Control), I is a curve of residual oxygen concentration in four gas foaming material groups for 2 hours without placing any material as a control (Control), J is a curve of H2O2 produced by four gas foaming material groups for 2 hours without placing any material as a control (Control);

[0031] Figure 3 Figures 2 and 3 are the in vitro biocompatibility and angiogenesis results of GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA; wherein, A is the Mg-MOF release spectrum of GOx-MOF / HAP-GelMA in PBS for 21 days, B is the cell viability of HUVECs co-cultured with various concentrations of Mg-MOF or normal cell culture medium for 48 hours, C is the cell viability of HUVECs co-cultured with four gas foam material extracts or no material for 48 hours, D is a fluorescence micrograph of double staining of live / dead cells cultured on four gas foam materials for 24 hours and 72 hours, E is a fluorescence image and phase contrast microscopy image of a tube formation experiment by co-culturing HUVECs with four gas foam material extracts or normal cell culture medium for 6 hours, F is a quantitative statistical graph of microtube length in each group, and G is a quantitative statistical graph of nodes in each group;

[0032] Figure 4Figure 2 is the in vitro experimental results of cell adhesion, proliferation and bioactivity of GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA gas foam materials; A is the SEM image of BMSCs, HUVECs and RAW264.7 macrophages cultured on the four gas foam materials for 72 hours, and B is the osteogenic genes (BMP2, ALP, O) of BMSCs cultured on the four air foam materials for 7 days without adding materials as the control group (Control). CN, RUNX2) expression results statistical graph, C is the expression results of angiogenesis genes (VEGF, BFGF, HIF-1α, CD31) of HUVECs on four gas foaming materials for 72 hours without adding materials as the control group (Control), D is the expression results of inflammatory genes (iNOS, IL-6, TNF-α, IL-1β) of HUVECs on four gas foaming materials for 72 hours without adding materials as the control group (Control);

[0033] Figure 5 The figure shows the results of GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA regulating the diabetic microenvironment in vivo to promote bone regeneration; wherein, A is the micro-CT 3D reconstructed image and cross-sectional image of the skull sample at week 12 after implantation of GelMA, HAP-GelMA and GOx-MOF / HAP-GelMA without adding materials as the control group (Control), and the lines in the figure represent the obtained cross-sections, B is the quantitative analysis statistical graph of the BV / TV values ​​of each group, C is the quantitative analysis statistical graph of the BME values ​​of each group, D is the H&E staining image of the bone tissue of each group, and E is the Masson staining image of the bone tissue of each group;

[0034] Figure 6 Figure 1 is a graph showing the results of bone tissue immunofluorescence staining of GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA, and the cell nuclei were stained with DAPI (blue); wherein A is a graph showing anti-CD31 (green) immunofluorescence staining in each group, B is a graph showing anti-OPN (green) immunofluorescence staining in each group, C is a graph showing anti-CD206 (green) immunofluorescence staining in each group, D is a graph showing anti-iNOS (green) immunofluorescence staining in each group, E is a quantitative statistical graph showing the capillary density in each group, F is a quantitative statistical graph showing the fluorescence intensity of OPN in each group, G is a statistical graph showing the fluorescence intensity of CD206 in each group, and H is a quantitative statistical graph showing the fluorescence intensity of iNOS in each group;

[0035] Figure 7The schematic diagram of the hydrogel of the present invention for treating bone defects in diabetic patients is shown in the figure. The hydrogel is composited with a metal organic framework of gallic acid and magnesium ions and gas-foamed hydroxyapatite nanowires loaded with glucose oxidase. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is described in detail below with reference to the accompanying drawings. The embodiments of the present invention are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

[0037] Glucose oxidase (GOx) is a natural glycoprotein produced by certain fungi and insects, which catalyzes the decomposition of glucose and the consumption of oxygen, and reacts to produce gluconic acid and hydrogen peroxide (H2O2). In recent years, GOx has been widely studied and applied in the biomedical field as a new therapeutic platform. It has also been shown to have application potential in the treatment of diabetic wounds. Our previous studies have shown that combining GOx with 3D-printed bioscaffolds has a good effect in the treatment of diabetic bone defects. When rationally using GOx to treat certain diabetes-related diseases, it is important to consider that GOx produces excessive H2O2 while reducing glucose and oxygen consumption, thereby causing oxidative stress, which is a difficult factor in inhibiting tissue regeneration.

[0038] Gallic acid is a phenolic acid isolated from Cornus officinalis, which has a wide range of pharmacological activities, including anti-inflammatory and antioxidant activities, and inhibits MAPK, NF-κB, and AP-1 pathways. It has an immunomodulatory effect on LPS-stimulated RAW264.7 cells, inhibits the formation and function of osteoclasts in rankl-induced bone marrow mononuclear cells (BMMs) and RAW264.7 cells, and inhibits osteoclastogenesis by blocking Akt, ERK, and JNK pathways. It also inhibits the expression of markers associated with osteoclastogenesis, including activated T cell nuclear factor 1 (NFATc1), C-FOS, and cathepsin K (CTSK). Magnesium ions (Mg 2+ ) promotes osteogenic differentiation of mesenchymal stem cells by increasing autophagy activity. 2+ Calcium ion channels at concentrations below 100 μg / cm2 activate cell membranes and promote calcium deposition, which is essential for bone growth. Metal-organic frameworks (MOFs) are emerging as an attractive nanoplatform for controlled drug delivery. They are an emerging class of hybrid porous materials composed of metal ions or clusters bridged by organic linkers. Previous studies have used gallic acid with Mg 2+ The synthesized MOF, whose porous structure can carry GOx for drug delivery.

[0039] Compared with traditional orthopedic surgery, minimally invasive hand surgery can shorten the operation time, reduce the amount of blood loss to the patient during the operation, and have significantly better perioperative outcomes, including less pain and anesthetic use, fewer complications (such as surgical site sensation and venous thromboembolism), and shorter recovery time. The development of injectable scaffold materials for bone defect repair is of great significance. Glucose fluctuations are particularly harmful to tissue regeneration and may induce metabolic disorders and mitochondrial dysfunction, characterized by increased oxidative stress. This is necessary to create a relatively stable and favorable environment for bone regeneration.

[0040] The following embodiments of the present invention provide an injectable, UV-curable, gas-foamed multifunctional hydrogel based on GelMA and HAP-NWs, and a GOx-loaded (GOx-MOF)-loaded gallic acid and Mg 2+ Metal-organic framework (Mg-MOF). Figure 7 In the paper, it is called GOx-MOF / HAP-GelMA. It creates more options for minimally invasive bone repair surgery, and GOx-MOF / HAP-GelMA can be made into different shapes to adapt to the size of bone defects. After gas foaming, GOx-MOF / HAP-GelMA is immediately cured by ultraviolet light, keeping many large pores interconnected, simulating the cell matrix, and providing more space and support for cell growth and vascular regeneration. HAP-NWs help maintain the shape of the pores and enhance the hardness of the material, making it more suitable for bone repair. The calcium (Ca) and phosphorus (P) obtained by the degradation of HAP-NWs are beneficial to the reorganization of HAP into human bones and promote bone formation.

[0041] The sources of the main materials used in the following embodiments of the present invention are as follows:

[0042] Gelatin and gallic acid were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0043] GOx (>180 U / mg), sodium dihydrogen phosphate dihydrate (NaH2PO4·2H2O), calcium chloride (CaCl2), oleic acid, methanol, sodium hydroxide (NaOH), ethanol, magnesium chloride (MgCl2), and methacrylic anhydride were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0044] High-glucose and low-glucose Dulbecco's modified Eagle's medium (DMEM), RPMI 1640 cell culture medium, and fetal bovine serum (FBS) were purchased from Gibco (Carlsbad, UK).

[0045] HUVECs, Raw264.7 cells and mBMSCs were cultured in an incubator (37° C., 5% CO 2 ) with complete medium (cell culture medium containing 10% FBS and 1% penicillin-streptomycin).

[0046] The various test methods used in the following examples of the present invention are specifically described as follows:

[0047] 1) Preparation of HAP-NWs

[0048] 135mL water, 105mL oleic acid and 60mL methanol were magnetically stirred for 5 minutes. 150mL aqueous solution containing 10.5g NaOH was slowly added and stirred vigorously for 30 minutes. 120mL aqueous solution containing 3.33g CaCl2 and 180mL aqueous solution containing 9.36g NaH2PO4·2H2O were added respectively, mixed and placed in a muffle furnace (Sxi-8-10, Zhengzhou Xinhan Instrument Equipment Co., Ltd.), and reacted at 180°C for 24 hours. Afterwards, the white precipitate was obtained by washing three times with ethanol and deionized water and centrifuging (12000rpm, 10 minutes). The white precipitate was dried in an oven to obtain a white powder.

[0049] 2) Preparation of Mg-MOF and GOx-MOF

[0050] Mg-MOF was synthesized by hydrothermal method. 3.8g gallic acid and 1g MgCl2 were added to 50mL water, magnetically stirred for 10 minutes, and the pH of the solution was adjusted to 8 with 10mol / L NaOH. The color of the solution was observed to change from turbid milky white to transparent brownish yellow. The solution was placed in a muffle furnace at 50℃, 70℃ and 100℃ for 24 hours. It was centrifuged and washed twice with deionized water (12000rpm, 15 minutes, 4℃), and the obtained brown precipitate was placed in an oven to dry to obtain a gray-green powder.

[0051] 12.5 μg GOx and 60 mg Mg-MOF were dissolved in 20 mL deionized water and stirred with ultrasound at 4 °C for 4 h.

[0052] 3) Preparation of GelMA, HAP-GelMA, Gox / HAP-GelMA and GOx-MOF / HAP-GelMA

[0053] GelMA: 10 g of gelatin was added to 100 mL of deionized water and stirred in a 60 ° C constant temperature water bath until completely dissolved. 6 mL of methacrylic anhydride was slowly dripped, and then oscillated in a constant temperature oscillator at 50 ° C for 3 h, and then 400 mL of 50 ° C deionized water was added to dilute the reaction solution. The diluted solution was placed in a 8000-14000 Da dialysis bag and dialyzed in deionized water at 50 ° C for 1 week, and the deionized water was replaced every 4 hours. After the dialysis, the dialysate was placed in a refrigerator at -80 ° C overnight and freeze-dried for 3 days to obtain GelMA. A solution of 12.5% ​​or 50% (w / v) GelMA was prepared with PBS. Photoinitiator (LAP) powder was added to PBS to form 2.5% (w / v), and then added to the dissolved GelMA in a ratio of 9:1 and mixed thoroughly. It was foamed with two volumes of air using a three-way stopcock and photocured under a blue light source (405 nm).

[0054] HAP-GelMA: HAP-NWs were added to GelMA solutions with a concentration of 12.5% ​​(w / v) and 50% (w / v), respectively, with a weight ratio of HAP-NWs to GelMA of 1:10, and mixed thoroughly. The same method was used for foaming and photocuring.

[0055] GOx / HAP-GelMA: GelMA solution was prepared with 50 ng / mL GOx solution, and HAP-NWs were added to 12.5% ​​(w / v) and 50% (w / v) GelMA solutions, respectively. The same method was used for foaming and photocuring.

[0056] GOx-MOF / HAP-GelMA: GelMA solution was prepared with 240 μg / mL GOx-MOF solution, and HAP-NWs were added to 12.5% ​​(w / v) and 50% (w / v) GelMA solutions, respectively. The same method was used for foaming and photocuring.

[0057] 4) Mg-MOF characterization

[0058] Mg-MOF was dissolved in PBS at a series of concentrations of 10, 20, 30, 40, 50, 60, 70 and 80 μg / mL. A standard Mg-MOF curve was obtained using a microplate reader (SpectraMAX iD3; Molecular Devices LLC, USA). The absorption peak of Mg-MOF was obtained in the same way. The concentration of the Mg-MOF solution used in other experiments was then calculated according to the corresponding standard curve.

[0059] 5) Characterization of GelMA, HAP-GelMA, Gox / HAP-GelMA and GOx-MOF / HAP-GelMA

[0060] Glucose decomposition test Glucose concentration was measured using a glucose assay kit and O-toluidine. Hydrogen peroxide concentration was measured using a hydrogen peroxide assay kit. Oxygen consumption was measured using an oxygen meter (Leica)

[0061] 6) Mg-MOF release experiment

[0062] 80 mg of GOx-MOF / HAP-GelMA was immersed in 2 mL of PBS, placed in a 37°C constant temperature shaker, centrifuged at fixed time intervals (3750 rpm, 15 min, 37°C), and then 100 mL of supernatant was taken, and the OD value of 260 nm light wave was measured with a microplate reader (SpectraMAX iD3; Molecular Devices LLC, USA), and the concentration of Mg-MOF solution was calculated using a standard curve. After removing 100 mL of supernatant each time, 100 mL of PBS was immediately added.

[0063] 7) Mechanical testing

[0064] The compressive stress-strain curves of GelMA, HAP-GelMA, Gox / HAP-Gemma and Gox-MOF / HAP-GelMA were tested using a mechanical testing machine (GT-TCS-2000 universal material testing machine).

[0065] 8) Degradation rate test

[0066] GelMA, HAP-GelMA, Gox / HAP-Gemma and Gox-MOF / HAP-GelMA were immersed in PBS and placed in an incubator (37°C, 5% CO2). Samples were taken out at predetermined intervals, weighed and recorded after freeze drying. The degradation ratios were calculated as follows:

[0067] Degradation ratios=(Ww) / W×100%.

[0068] (w and w represent the weight of immersed sample and initial sample respectively)

[0069] 9) Cytotoxicity test

[0070] HUVECs were seeded in 96-well plates at 5000 cells per well and cultured in 100 mL DMEM containing 10% FBS. HUVECs were starved with 100 μL high-glucose DMEM for 12 h and then treated with different concentrations of Mg-MOF (40, 60, 80, 100, 120, and 140 μg mL–1) or no material (control group) for 48 h. Each group had triplicate similarity. After 48 h, complete medium containing 10% CCK-8 solution was added to each well to allow interaction with living cells. After 1 h of co-culture, cell viability was analyzed using a microplate reader (SpectraMAX iD3; Molecular Devices LLC, USA). GelMA, HAP-GelMA, GOx / HAP-GelMA, and GOx-MOF / HAP-GelMA were immersed in 5 mL of complete medium for three days to obtain the corresponding extracts. CCK-8 kit was used to measure the 72-hour viability of HUVECs grown with GelMA, HAP-GelMA, Gox / HAP-GelMA, and Gox-MOF / HAP-GelMA extracts. Complete medium without any material was used as a control group.

[0071] 10) Live / dead cell staining

[0072] GelMA, HAP-GelMA, Gox / HAP-GelMA, and Gox-MOF / HAP-GelMA were placed flat on the bottom of a 12-well plate. HUVECs were seeded at 10 × 104 cells per well in a 12-well plate. Calcein AM / PI assay (Yeasen, Shanghai, China) was prepared according to the manufacturer's protocol. After 72 hours of co-culture, the culture medium was removed and 1 mL of staining solution was added to each well. The 12-well plate was then placed in an incubator for 15 minutes. The cells were imaged using a fluorescence microscope.

[0073] 11) Microtubule formation assay

[0074] First, according to the manufacturer's protocol, 50 μL of growth factor-reduced Matrigel (BD Biosciences, USA) was added to each well of a 96-well plate and then placed in an incubator for 30 minutes to solidify the Matrigel. 4 Cells were seeded on a solidified Matrigel matrix and cultured in serum-free DMEM containing GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA extracts or without materials (control group). Representative images of each group were taken at 6 hours after treatment. Live cell staining was performed in the same manner. Cells were imaged using a fluorescence microscope.

[0075] 12) Observe the cell morphology on the scaffold using scanning electron microscopy (SEM)

[0076] GelMA, HAP-GelMA, Gox / HAP-GelMA and Gox-MOF / HAP-GelMA were placed flat on the bottom of a 48-well plate. HUVECs were plated at 2×10 cells per well. 4 RAW264.7 cells were seeded in 48-well plates at a rate of 5×10 cells per well. 4 mBMSCs were seeded in 48-well plates at 3×10 per well. 4 cells were seeded in 48-well plates. The three cells were cultured under classical conditions for 72 h. Briefly, all samples were fixed in 2.5% glutaraldehyde for 4 h and rinsed three times with PBS. Then, gradient dehydration was applied using ethanol concentrations of 30%, 50%, 70%, 80%, 90%, 95% and 100%. The samples were placed in an oven at 40 ° C overnight. The obtained samples were sputter coated with gold and evaluated by SEM.

[0077] 13) In vitro qRT-PCR detection

[0078] HUVECs were plated at 40 × 10 4 RAW264.7 cells were seeded in 6-well plates at a rate of 60 × 10 cells per well and cultured in 2 mL DMEM containing 10% FBS. 4 mBMSCs were seeded in 6-well plates and cultured in 2 mL RPMI 1640 containing 10% FBS. 30 × 10 mBMSCs were plated in each well. 4 The cells were seeded in 6-well plates at a rate of 10 cells / mL and cultured in 2 mL low glucose DMEM containing 10% FBS. All three cells were starved in the corresponding serum-free medium for 12 h and then treated with GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA extracts or without any material treatment (control group). HUVECs, RAW264.7 and mBMSCs were cultured for 72 h, 72 h and 2 weeks, respectively. The expression levels of VEGF, BFGF, HIF-1α and CD31 genes were measured in HUVECs, iNOS, IL-6, TNF-α and IL-1β genes were measured in RAW264.7, and RUNX2, OSX, BMP2 and ALP genes were measured in mBMSCs.

[0079] 14) Critical size skull defect model

[0080] Diabetic bone defect model was established using diabetic (db / db) mice (Nanjing Institute of Biomedical Sciences, Nanjing University, China) (6 weeks old). All animal study protocols were approved by the Institutional Animal Care and Experiment Committee of Shanghai Jiao Tong University School of Medicine. Fifteen mice were randomly divided into five groups (control group, GelMA group, HAP-GelMA group, GOx / HAP-GelMA group, and GOx-MOF / HAP-GelMA group). After anesthesia, the skull was exposed through a sagittal incision (1 cm) in the middle of the scalp. Bone defects were created using a 3 mm diameter trephine, and the incision was closed after implantation of the material.

[0081] 15) Histology and immunohistochemistry staining

[0082] Micro-CT imaging and histopathological analysis were performed 12 weeks after surgery. In detail, the defect sites were dissected, fixed in 4% paraformaldehyde, and subsequently scanned by a Micro-CT machine (Scanco Medical AG, Switzerland). After micro-CT scanning, 3D isosurface rendering was used for bone visualization, and the percentage of new bone volume relative to tissue volume (BV / TV) and bone mineral density (BMD) were determined. Major organs (heart, liver, spleen, lungs, and kidneys) were harvested for H&E histological analysis.

[0083] H&E and Masson trichrome staining were used to detect the repair of bone defects. This example uses CD31 and OPN antibodies to test the effects of these materials on angiogenesis and osteogenesis in diabetic mice. iNOS and CD206 antibody markers are used to test the effects of these materials on inflammation in diabetic mice.

[0084] 16) Data analysis

[0085] All quantitative data are presented as mean ± SD, n = 3 per group. Unpaired Student t test was used for two groups, and one-way ANOVA with Tukey post hoc test was used for more than two groups. Statistical analysis was performed using SPSS (Statistical Package for Social Sciences) 26.0, and two-sided p < 0.05 was considered statistically significant. * indicates p < 0.05, ** indicates p < 0.01, *** indicates p < 0.001, and **** indicates p < 0.0001. Differences were considered statistically significant.

[0086] GraphPad Prism 8.0 (GraphPad Software, USA) was used to draw graphs.

[0087] ImageJ software (NIH, Bethesda, MD, USA) was used for imaging and statistical analysis.

[0088] Example 1 Synthesis and Characterization of Mg-MOF and HAP Nanoparticles

[0089] Mg-MOF was synthesized by hydrothermal method. Mg-MOF was originally a kind of poly(methylenediaminetetrafluoroethylene) with gallic acid as the skeleton. 2+ Metal organic framework material with intersection. It has the special property of being porous. GOx is loaded by Mg-MOF to obtain GOx-MOF, thereby achieving drug delivery ( Figure 1 A). In previous studies, Mg-MOF was successfully synthesized at a high temperature of 120°C using gallic acid as raw material. In order to further optimize the material quality and protect the biological activity of gallic acid, Mg-MOF was synthesized at 50°C and 70°C by hydrothermal method, and the obtained precipitated powder was used for XRD ( Figure 1 B).

[0090] The results show that Mg-MOF with the same crystal structure can be synthesized at these three temperatures, which proves the conclusion that Mg-MOF can be successfully synthesized at lower temperatures. The absorption spectrum of Mg-MOF has an independent absorption peak at 260nm. GOx has an independent absorption peak at a wavelength of 276nm, and GOx is loaded onto Mg-MOF to obtain GOx-MOF. The absorption peak of GOx-MOF has an independent absorption peak at 272nm between Mg-MOF and GOx ( Figure 1 C). The absorbance values ​​of Mg-MOF of different concentrations were measured at 260 nm, and a standard curve was constructed based on the absorbance values ​​for calculating the concentration of Mg-MOF in subsequent experiments ( Figure 1 D).

[0091] HAP-NWs were synthesized by hydrothermal method, e.g. Figure 1 E. HAP NWs are insoluble in water and ethanol. From the scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images, it can be observed that HAP is a long fiber with a diameter of about 7-9 nm, with different lengths and distributed in clusters ( Figure 1 F and 1G). X-ray diffraction (XRD) results showed that it had characteristic peaks and was the synthetic crystal of NAP-NWs ( Figure 1 H). When placed in deionized water, HAP-NWS looked like a fluffy white cloud that settled at the bottom of the bottle ( Figure 1 I).

[0092] Example 2 Synthesis and Characterization of GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA

[0093] As is known, GelMA hydrogel is initially colorless and transparent. Through gas foaming, the refractive index of GelMA increases with the integration of small bubbles, presenting a slightly transparent white color. After mixing with HAP-NW, the refractive index of GelMA further increases, and HAP-GelMA presents an opaque white color. In addition, when GOx is mixed with HAP-GelMA, its appearance does not change significantly. When GOx-MOF is mixed with HAP-GelMA, the color of the gas foaming material changes to a very light green when observed with the naked eye, and it is even impossible to distinguish the colors of GOx / HAP-Gemma in optical photographs ( Figure 2 A). Their microstructures were observed using a scanning electron microscope. The gas foaming material of GelMA with a concentration of 12.5% ​​showed a vesicular structure, with an average vacuolar diameter of about 100 μm, and many pores connecting the vacuoles. The vesicle structure of the GelMA group showed a certain degree of collapse and deformation.

[0094] The vesicle structure of the GelMA group showed a certain degree of collapse and deformation, while the vesicle structure of the HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA groups was firm and intact. The same bubble structure was observed in the microstructure of the gas foam with a GelMA concentration of 50%, in which a large number of pores were connected between the vacuoles. In locations where there was not sufficient foaming, it was observed that the freeze-dried pores of the GelMA hydrogel with a 50% concentration were very small and insufficient to accommodate cell growth. However, after gas foaming, it changed this situation, increasing the vacuolar size and porosity of the material, which was more suitable for cell growth ( Figure 2 B). As the concentration of GelMA increases, the stiffness of the material increases. The addition of HAP-NWs provides a scaffold that makes the structure similar to reinforced concrete, which not only increases the pore filling and stiffness, but also improves the stiffness of the material ( Figure 2 C).

[0095] In addition, the mechanical properties of the gas foamed materials were tested and it was found that the maximum stresses borne by GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA were 26.36N, 164.97N, 152.96N and 158.38N, respectively. Figure 2D). The gas foam material containing only GelMA was compared with the gas foam material with HAP-NW added. The maximum load stress of HAP-GelMA, GOx / HAP-Gemma and GOx-MOF / HAP-GelMA increased by 6.26, 5.80 and 6.01 times, respectively. It is more suitable as a promising bone repair material. Traditional bone defect repair surgery causes great damage and trauma to human skin and muscle tissue. Injectable bone defect repair materials combined with UV curable materials are expected to solve this problem. The material is injected to fill the defective bone tissue, and then the UV fiber is inserted along the injection hole to achieve minimally invasive repair ( Figure 2 E and 2F).

[0096] Traditional bone defect repair involves implanting metal and bone cement fillers, some of which require a second surgical procedure to remove the fixation. Degradable bone defect repair materials are expected to solve this problem. As the material degrades, autologous bone tissue can grow to fill the defect. In this regard, this example has verified the in vitro degradability of GOx-MOF / HAP-GelMA. The results showed that on day 28, the average degradation rate of the gas foaming material in the GelMA group was 65.28%, and the degradation rates of the HAP-GelMA and GOx / HAP-GelMA groups were roughly the same, at 13.19% and 14.34%, respectively. On day 28, the degradation of the GOx-MOF / HAP-GelMA group was relatively mild, with an average of 25.87% ( Figure 2 G). The degradation rates of GelMA on day 28 were 4.95, 4.55, and 2.52 times those of HAP-GelMA, GOx / HAP-GelMA, and GOx-MOF / HAP-GelMA groups, respectively.

[0097] A moderate degradation rate is more conducive to the growth of bone tissue, and it will not be completely degraded and lose support before the bone tissue grows. In the pathophysiological mechanism of the diabetic microenvironment affecting bone defect repair, hyperglycemia and chronic inflammation lead to the formation of advanced glycation end products and increased production of reactive oxygen species, which in turn lead to the disruption of the balance between osteoblasts and osteoclasts, resulting in reduced bone formation and affecting bone defect repair. Lowering blood sugar and reducing ROS are two key points to improve the diabetic bone regeneration microenvironment. GOx can consume glucose and oxygen (O2) to produce gluconic acid and H2O2, and gallic acid is slowly released from Mg-MOF with excellent antioxidant properties.

[0098] Hypoxic environment promotes angiogenesis. Therefore, the performance of four gas foaming materials was tested in vitro under reduced glucose, hydrogen peroxide and oxygen content. A grape solution without any substance was set to the same concentration as a control. In the GOx-MOF / HAP-GelMA group, normal blood glucose levels dropped from 12.83mmol / L to 5.65mmol / L on average within 48 hours. The blood glucose lowering efficiency of the GOx-MOF / HAP-GelMA group was significantly higher than that of the GOx / HAP-GelMA group, which was attributed to the cascade reaction of glucose depletion and H2O2 depletion. The glucose concentrations in the GelMA group and the HAP-GelMA group also decreased slightly ( Figure 2 H).

[0099] Meanwhile, the trend of O2 consumption was similar to that of glucose consumption, and the GOx-MOF / HAP-GelMA group consumed O2 more efficiently than the GOx / HAP-GelMA group. The gas foaming materials of GelMA and HAP-GelMA groups had basically no effect on O2 reduction ( Figure 2 I). In addition, in the gas foaming material GOx / HAP-GelMA group, the average H2O2 produced after 48 hours of accumulation was 48.13 μm / L. The average H2O2 concentration produced by the gas foaming material GOx-MOF / HAP-GelMA group was at a safe level of 22.49 μmol / L (<30 μm / L). In contrast, the gas foaming materials GelMA and HAP-GelMA did not produce H2O2 ( Figure 2 J). It can be seen that this is basically consistent with the expectations of the experimental design.

[0100] The above experiments have confirmed that the gas foaming material GOx-MOF / HAP-GelMA reduces glucose, reduces H2O2, depletes O2, and is expected to effectively regulate the microenvironment of diabetic bone regeneration in vivo.

[0101] Example 3 In vitro biocompatibility and angiogenesis of GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA

[0102] In order to investigate the biocompatibility of GOx-MOF / HAP-GelMA, the cumulative release of Mg-MOF from GOx-MOF / HAP-GelMA was first tested. In the experiment, it was observed that the release of Mg-MOF was slow within 5 days, and the release efficiency increased from the 5th to the 10th day, and then gradually slowed down from the 10th to the 21st day ( Figure 3A). It can be concluded that GOx-MOF / HAP-GelMA achieves the delivery and sustained release of Mg-MOF. In addition, the survival rate of human umbilical vein endothelial cells (HUVECs) was tested by CCK-8 experiment. The results showed that the Mg-MOF concentration of 120 μg / mL had the best effect on the proliferation of HUVECs ( Figure 3 B).

[0103] Therefore, in the following experiments, the concentration of Mg-MOF in the GOx-MOF / HAP-GelMA extract was taken as 120 μg / mL unless otherwise specified. The same CCK-8 experiment was performed with extracts of GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA to verify the cytotoxicity of the gas foaming materials. The results showed that, except for the GOx / HAPGelMA group, the other three groups had a slight promoting effect on the proliferation of HUVECs, among which the cell survival rate of the GOx-MOF / HAP-GelMA group was significantly different from that of the control group, indicating that the GOx-MOF / HAP-GelMA group had a significant effect on promoting cell proliferation ( Figure 3 C).

[0104] The analysis of its mechanism of action should be the low oxygen environment and the Mg released by the GOx-MOF / HAP-GelMA group material. 2+ Under classical conditions, cells were cultured on gas foam materials for 1 and 3 days and double-stained for live / dead cells. The results were similar to those of the CCK-8 experiment, in which a relatively large number of erythrocyte death could be observed in the GOx / HAP-GelMA group, while erythrocyte death was relatively rare in the other three groups ( Figure 3 D). The reason is that the H2O2 produced by the GOx / HAP-GelMA group killed the cells, while the H2O2 produced by the GOx-MOF / HAP-GelMA group was removed by gallic acid and protected the cells.

[0105] Angiogenesis plays an important role in bone regeneration and bone defect repair. In this regard, this example verifies the angiogenesis effect of the four gas foaming materials in vitro through tube formation experiments. The complete cell culture fluid of the material-free group was also used as a control group, and the other four groups were tested with extracts. The results showed that the four gas foaming material groups were significantly better than the control group in promoting HUVECs tube formation. Among them, the GOx-MOF / HAP-GelMA group had the most significant promoting effect, with the tube length being 1.29 times that of the control group and the number of nodes being 1.98 times that of the control group. In the GelMA, HAP-GelMA and GOx / HAP-GelMA groups, the tube lengths were 1.08, 1.14 and 1.20 times that of the control group, respectively, and the nodes were 1.24, 1.47 and 1.62 times that of the control group, respectively ( Figure 3 E-3G).

[0106] Analysis of these results shows that GelMA itself has a certain angiogenic effect, and GOx / HAP-GelMA and GOx-MOF / HAP-GelMA create a low O2 environment that is conducive to the formation of tubes. After adding Mg-MOF to GOx / HAP-GelMA, high Mg 2+ and low H2O2 environment further promotes the tube-forming effect.

[0107] Example 4 In vitro experiments on cell adhesion, proliferation and bioactivity of GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA gas foam materials

[0108] The adhesion and growth of three different cell types (mouse bone marrow mesenchymal stem cells (mBMSCs), HUVECs, and RAW264.7 macrophages) on four gas foaming materials were observed. The three cell types were seeded on GelMA, HAP-GelMA, GOx / HAP-GelMA, and GOx-MOF / HAP-GelMA, respectively, and cultured under classical conditions for 72 hours, and then observed by SEM ( Figure 4 A). All three cells were observed to adhere well to the materials. mBMSCs and HUVECs expanded adequately in HAP-GelMA, GOx / HAP-GelMA, and GOx-MOF / HAP-GelMA containing HAP-NWs, while cells expanded weakly on materials containing GelMA alone. This is thought to be a result of the weaker support of bubbles and pores in the gas-foamed materials containing GelMA alone. The reinforced concrete structure formed by the addition of HAP-NWs provided better support for the bubble pores and provided hard fiber adhesion points for the cells. On GOx / HAP-GelMA, the number of cell proliferation of all three types was relatively small compared to the other three materials, which is also thought to be caused by the excessive production of H2O2.

[0109] HAP is an important component of human skeleton. The shape and texture of HAP-NWs and human HAP are still different, but the slow decomposition of HAP-NWs can provide useful Ca and P for bone formation, thereby promoting bone regeneration and repairing bone defects. mBMSCs were seeded on the four materials and cultured under classical conditions for 7 days to analyze the effects of the materials on the differentiation of mBMSCs, while no material was added as a control group. Quantitative real-time PCR (qRT-PCR) was used to quantify the expression of osteogenic genes in mBMSCs ( Figure 4 B).

[0110] This example studies the osteogenic differentiation of mBMSCs induced by the control group (Control), GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA. The expression of osteogenic genes runt-related transcription factor 2 (RUNX2), bone filaments (OSX), alkaline phosphatase (ALP) and bone morphogenetic protein 2 (BMP2) was measured respectively. The results showed that the group containing HAP-NWs expressed more osteogenic genes. In particular, the GOx-MOF / HAP-GelMA group combined with Mg 2+ , gallic acid and HAP-NWs induced osteogenic differentiation, and the expression of osteogenic genes was more significant.

[0111] In general, GOx-MOF / HAP-GelMA substantially enhanced the proliferation of mBMSCs and stimulated osteogenic differentiation. HUVECs were seeded on four foaming materials (GelMA, HAP-GelMA, GOx / HAP-GelMA, and GOx-MOF / HAP-GelMA) and cultured for 72 h under classical conditions without adding materials as a control group. qRT-PCR was used to quantify the effect of each material on the gene expression of HUVECs, thereby studying and demonstrating the role of the material in promoting angiogenesis in vitro. The results showed that the materials GOx / HAP-GelMA and GOx-MOF / HAP-GelMA had good advantages in inducing the gene expression of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (BFGF), hypoxia-inducible factor-1α (HIF-1α), and CD31, due to the hypoxic environment induced by GOx ( Figure 4 C).

[0112] The angiogenic gene expression induced by GOx-MOF / HAP-GelMA was the most favorable, which was also attributed to the low O2 content environment and high Mg provided by GOx-MOF. 2+environment, coupled with the removal of harmful H2O2 in the cascade reaction, further demonstrated the advantages of GOx-MOF / HAP-GelMA. qRT-PCR was used to quantify the induction of inflammatory gene expression in RAW264.7 cells by the four foaming materials, thus confirming the ability of these materials to modulate inflammation in vitro. RAW264.7 cells were also seeded on GelMA, HAP-GelMA, GOx / HAP-GelMA, and GOx-MOF / HAP-GelMA, and gene expression was quantified after 3 days of culture under classical conditions without the addition of materials as a control group. The results showed that the expression of inducible nitric oxide synthase (iNOS), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and interleukin-β (IL-1β) genes was significantly increased in the GOx / HAP-GelMA group. The iNOS gene expression in the GOx-MOF / HAP-GelMA group was 5.26 times lower than that in the control group. The IL-6 gene expression in the GOx-MOF / HAP-GelMA group was not significantly different from that in the control group. The TNF-α gene expression in the GOx-MOF / HAP-GelMA group was 2.46 times lower than that in the control group. The IL-1 gene expression in the GOx-MOF / HAP-GelMA group was not significantly different from that in the control group. Figure 4 D). Thus, in the GOx / HAP-GelMA group supplemented with GOx only, excessive H2O2 production led to high expression of inflammatory genes. After the addition of gallic acid, the cascade reaction of the gas foaming material GOx-MOF / HAP-GelMA consumed the excess H2O2 produced by GOx decomposing glucose and O2. From the results, the expression of inflammatory genes in the GOx-MOF / HAP-GelMA group was mostly lower than that in the control group. It can be seen that gallic acid can consume the H2O2 produced by GOx, and it also further removes some other ROS that already exist.

[0113] Example 5 GOx-MOF / HAP-GelMA regulates the diabetic microenvironment in vivo to promote bone regeneration

[0114] The gas foaming materials GelMA, HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA were implanted into skull defects of mice, and the heart, liver, spleen, lungs and kidneys of diabetic mice fed for 3 months under classical conditions (specific pathogen-free (SPF) conditions with sufficient food and water) were used to explore the biocompatibility of the materials in animals. The results showed that no pathological changes occurred in the important organs of the mice after the implantation of the materials. The four materials were shown to be biocompatible in diabetic mice.

[0115] In order to verify the promoting effect of the four gas foaming materials on the repair of skull defects in vivo, a skull defect model without implanted materials was established as a control. After the mice were fed under specific pathogen-free (SPF) conditions with sufficient food and water for 12 weeks, the skulls of the diabetic mice in each group were scanned by X-ray micro-computed tomography (Micro-CT). Figure 5 As shown in A, there was almost no bone regeneration and repair in the defects of the control and GelMA groups, reflecting the difficulty of bone regeneration and bone repair in the diabetic microenvironment. Partial bone regeneration was observed in the HAP-GelMA, GOx / HAP-GelMA and GOx-MOF / HAP-GelMA groups, among which the GOx-MOF / HAP-GelMA group had the most superior bone regeneration, followed by the HAP-GelMA group with only HAP-NW added, and the GOx / HAP GelMA group was the lowest. Although there was some bone regeneration and repair in the GOx / HAP-GelMA group, the residual area of ​​the bone defect was still large. Quantitative analysis of bone volume / total volume (BV / TV) showed that the GOx-MOF / HAP-GelMA group was 6.08, 5.69, 1.40 and 1.68 times that of the control group (Control), GelMA, HAP-GelMA and GOx / HAP-GelMA, respectively ( Figure 5 B). Quantitative analysis of bone mineral density (BME) showed that the GOx-MOF / HAP-GelMA group was 6.87, 6.71, 1.39 and 1.80 times higher than the control group GelMA, HAP-GelMA and GOx / HAP-GelMA, respectively ( Figure 5 C)

[0116] The bone tissue at the skull defect site was observed by H&E and Masson's trichrome staining ( Figure 5 D and Figure 5 E). In the control group (Control), all defects were filled with fibrous connective tissue, while in the GelMA group, except for a small amount of GelMA residue that was not completely degraded, the remaining defects were also filled with fibrous connective tissue, and almost no new bone tissue was found. It can be observed that the defects in the HAP-GelMA group are basically filled with new bone tissue, and it can be observed that part of the defects in the GOx / HAP-GelMA group are filled with new bone tissue and the other part is filled with connective tissue. The GOx-MOF / HAP-GelMA group has the best repair effect, with almost no residual bone defects, completely filled with new bone tissue, and some mature bone tissue can also be observed. This shows that the bone defects in the GOx-MOF / HAP-GelMA group began to be repaired preferentially and have a state of continuous repair.

[0117] It can be seen that in the presence of Ca and P (produced by HAP-NWs degradation), the bone defect repair benefit is considerable, and through the cascade reaction of GOx-MOF, the diabetic bone tissue microenvironment is regulated, making the bone repair steps more inclined to normal bone regeneration and bone tissue defect repair.

[0118] Example 6 Osteogenesis, angiogenesis and anti-inflammatory activities of GOx-MOF / HAP-GelMA in vivo

[0119] Immunofluorescence staining for CD31 (vascular marker), osteopontin (OPN) (bone marker), CD206 (pro-healing M2 macrophage marker), and iNOS (pro-inflammatory M1 macrophage marker) ( Figure 6 ). CD31 marked the blood vessel density in the bone tissue defect site of different research groups. From the representative images, it can be observed that the green distribution was significantly higher in the GOx / HAP-GelMA group and the GOx-MOF / HAP-GelMA group ( Figure 6 A), quantitative analysis results showed that the vascular density of the GOx-MOF / HAP-GerlMA group was 5.80, 5.80, 3.63 and 1.45 times that of the control group, GelMA, HAP-GelMA and GOx / HAP GelMA, respectively ( Figure 6 E). OPN participates in bone formation and represents the active behavior of osteoblasts and osteoclasts. Representative images of OPN immunofluorescence staining from different research groups can be visually found, indicating that the (green) staining area of ​​the GOx-MOF / HAP-GelMA group is more obvious than that of the other groups ( Figure 6 B). Quantitative analysis of OPN markers showed that the GOx-MOF / HAP-GelMA group was 3.32, 2.71, 1.44, and 2.07 times that of the control group GelMA, HAP-GelMA, and GOx / HAP-GelMA, respectively ( Figure 6 F). iNOS and CD206 mark the polarization type of macrophages and represent the in vivo regulation of inflammation. In the early stage of inflammation and in the diabetic microenvironment, macrophages are mainly polarized to M1, while in normal organisms and in the late stage of inflammation, macrophages are mainly polarized to M2, which is more conducive to tissue repair.

[0120] Therefore, this example uses these two markers in different research groups to explore the regulation of gas foam materials on bone regeneration inflammation in the diabetic microenvironment. It can be observed from the representative images that the green staining area of ​​CD206 is more obvious in the GOx-MOF / HAP-GelMA group, and the green staining area of ​​iNOS is more significant in the other groups ( Figure 6C and 6D). Quantitative results showed that the CD206 of the GOx-MOF / HAP-GelMA group was 1.63, 1.60, 1.47, and 1.75 times that of the control group, GelMA, HAP-GelMA, and GOx / HAP-GelMA, respectively ( Figure 6 H). In contrast, the iNOS fluorescence quantification of the GOx-MOF / HAP-GelMA group was 2.08, 1.81, 1.93, and 2.80 times that of the control group GelMA, HAP-GelMA, and GOx / HAP-GelMA, respectively ( Figure 6 I).

Claims

1. A hydrogel, characterized in that Includes hydroxyapatite nanowires and basic materials for forming hydrogels.

2. The hydrogel according to claim 1, characterized in that The weight ratio of the hydroxyapatite nanowires to the basic material of the hydrogel is 1:

10.

3. The hydrogel according to claim 1, characterized in that The basic material of the hydrogel is GelMA.

4. The hydrogel according to claim 1, characterized in that The hydroxyapatite nanowires are prepared as follows: After mixing water, oleic acid and methanol, add aqueous solution of NaOH, stir, add CaCl2 and NaH2PO4·2H2O, mix, place at 180℃ for reaction for 24 hours, wash and centrifuge to obtain precipitate, and obtain; The cleaning is carried out by using ethanol and deionized water alone or in combination.

5. The hydrogel according to claim 1, characterized in that GOx was also included. By weight, the ratio of GOx and HAP-NWs was 1±0.2:2×10 5 .

6. The hydrogel according to claim 1, characterized in that Also included is Mg-MOF, which is composed of gallic acid and Mg 2+ Prepared, by weight, the gallic acid and Mg 2+ is 15±1:1, and the ratio of the gallic acid to the HAP-NWs is 1:42±2.

7. The hydrogel according to claim 1, characterized in that Also includes GOx, gallic acid, Mg 2+ , gallic acid and Mg 2+ Mg-MOF was formed, and GOx was loaded on Mg-MOF. By weight, the ratio of GOx to HAP-NWs was 1±0.2:2×10 5 , the gallic acid and Mg 2+ is 15±1:1, and the ratio of the gallic acid to the HAP-NWs is 1:42±2.

8. Use of the hydrogel according to claim 1 in preparing bone defect medical devices.

9. The use according to claim 8, characterized in that The bone defect is a bone defect caused by diabetes.

10. A medical device, characterized in that Comprising the hydrogel according to claim 1.

Citation Information

Cited By

  • Multi-dimensional bionic scaffold with space-time synergistic osteogenesis function and preparation method

    CN120754327A

  • Composite hydrogel and application thereof in preparation of diabetes wound repair dressing

    CN120884735A

  • A composite hydrogel and its application in the preparation of a diabetic wound repair dressing

    CN120884735B

  • Blood glucose response type hydrogel

    CN120983700A

  • Magnesium alloy composite scaffold as well as preparation method and application thereof

    CN122163895A